051 Peripheral nerve blocks in combination with onabotulinum toxin A treatment to improve migraine outcomes. Issue 6 (27th May 2022) - Germain, Lewis; Hilton, James; Amores, Fred; Fernandes, Linford; Randall, Marc; Idrovo, Luis
Abstract : There is no evidence base on the efficacy of onabotulinum toxin A treatment and peripheral nerve blocks (PNBs) when used in combination to treat chronic migraine. This retrospective single centre evaluation looked at outcomes from 198 headache service users who had been managed with onabotulinum toxin A treatment alone (n=97), PNBs alone (n=43) or both treatments in combination (n=58). 85% of patients who had PNBs alone considered them effective in reducing their headache burden on follow-up, compared to 71% of patients who had onabotulinum toxin A treatment only. In patients who received both headache treatments, due to increased headache burden, 84% of patients found PNBs effective, while 41% of patients found onabotulinum toxin A treatment effective, suggesting that PNB respond- ers don't always respond to onabotulinum toxin A treatment. There were also differences in the type of headache outcomes reported, with patients who received PNBs more likely to report a reduction in headache severity compared to patients who received onabotulinum toxin A treatment (69% vs. 50%). Patient who received onabotulinum toxin A treatment were more likely to report a reduction in headache days (47% vs 0.31%). Complications rates and side effects were also evaluated. linford.fernandes@nhs.net|ABN Bursary